2004
DOI: 10.1109/jsac.2004.830889
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Sources Over Wireless Channels: Cooperative Source-Channel Coding

Abstract: Abstract-We consider wireless sensor networks deployed to observe arbitrary random fields. The requirement is to reconstruct an estimate of the random field at a certain collector node. This creates a many-to-one data gathering wireless channel. One of the main challenges in this scenario is that the source/channel separation theorem, proved by Shannon for point-to-point links, does not hold anymore. In this paper, we construct novel cooperative source-channel coding schemes that exploit the wireless channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…He showed that transmitting uncoded observations in the Gaussian MAC gives the best scaling law. Other relevant work includes source compression for detection or estimation under communication rate constraints (e.g., [4]- [8]) and joint source-channel coding for the MAC (e.g., [9]- [11]). The information theoretic approach considers the asymptote that the amount of source data/channel resources is large.…”
Section: Related Workmentioning
confidence: 99%
“…He showed that transmitting uncoded observations in the Gaussian MAC gives the best scaling law. Other relevant work includes source compression for detection or estimation under communication rate constraints (e.g., [4]- [8]) and joint source-channel coding for the MAC (e.g., [9]- [11]). The information theoretic approach considers the asymptote that the amount of source data/channel resources is large.…”
Section: Related Workmentioning
confidence: 99%
“…Many problems are analyzed within an information theoretic setting, such as distributed source coding, CEO [4] and sensor networks. A connection between these rate-distortion problems to network scenarios is reported in [5], [6], [7]. The CEO setting is also addressed by tools of estimation theory (where it is commonly referred to as fusion center), such as [8], [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…For this problem he derived sufficient conditions for the achievability of a distortion pair. More recently, another variation where the two source components are binary with Hamming distortion and where the multiple-access channel is Gaussian was considered by Murugan, Gopala and El Gamal [10] who derived sufficient conditions for the achievability of a distortion pair. Gastpar [11] considered a combined source-channel coding analog of the quadratic Gaussian CEO problem.…”
Section: Introductionmentioning
confidence: 99%